Contribution of IL‐12A and IL‐12B Polymorphisms to Chlamydia trachomatis‐Specific Cell‐Mediated Immune Responses. (March 2015) - Öhman, H.; Natividad, A.; Bailey, R.; Ragoussis, J.; Johnson, L.‐L.; Tiitinen, A.; Halttunen, M.; Paavonen, J.; Surcel, H.‐M.
Abstract Inherited variance in the IL‐12B gene is associated with susceptibility to Chlamydia trachomatis‐induced tubal factor infertility and disease severity. In this study, our aim was to discover how polymorphisms in IL‐12‐coding genes influence C. trachomatis‐induced immune responses and IL‐12 production. The study population consisted of 240 women. IL‐12A and IL‐12B single nucleotide polymorphisms (SNPs) were determined from isolated DNA using the Sequenom system with matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectrometry. We studied lymphocyte proliferative (LP) responses to C. trachomatis strains E and F elementary bodies (EBs) and recombinant chlamydial heat‐shock protein 60 (CHSP60) antigen. IL‐12p40 and IL‐12p70 levels were measured using the BD Flex Set method. We found a statistically significant association between the C. trachomatis EB antigen‐specific LP response and the rs2853694 SNP (P = 0.02). Our study demonstrates that the IL‐12 cytokine family is involved in C. trachomatis‐specific immune responses. Moreover, C. trachomatis‐induced IL‐12 production and the IL‐12B rs2853694 SNP partially explain individual variation in the C. trachomatis LP response.